RNF43 Mutations in IPMN Cases: A Potential Prognostic Factor - Xiao Yan Chang; Yan Wu; Ying Jiang; Peng Yan Wang; Jie Chen (Gastroenterology Research and Practice)
An intraductal papillary mucinous neoplasm (IPMN) is a common pancreatic precursor lesion, and it often harbors mutations in KRAS, GNAS, and RNF43. To clarify the molecular profiles of IPMNs, we conducted mutation analysis of KRAS, GNAS, and RNF43 in 61 IPMN formalin-fixed, paraffin-embedded (FFPE) specimens. The mutation rates of codons 12, 13, and 61 in KRAS and codon 201 in GNAS were detected by Sanger sequencing. Next-generation sequencing was performed on RNF43, and the results were further verified by Sanger sequencing. We identified KRAS and GNAS mutations in 35 (57%) and 40 (66%) IPMN cases, respectively. GNAS mutations were significantly correlated with the morphologic subtype (P<0.001) and were more prevalent in the intestinal subtype (93%) than in the gastric (55%) and pancreatobiliary subtypes (44%) but were absent in the oncocytic subtype. RNF43 mutations were found in 5 cases (8%), all of which occurred in high-grade dysplasia and invasive lesions (2/5 and 3/5). All 5 cases harboring RNF43 mutations also exhibited GNAS mutations. RNF43 mutations were associated with a worse prognosis in invasive IPMN patients (P=0.002), while KRAS and GNAS mutations did not affect the prognosis of patients.